2008
DOI: 10.1136/jme.2007.023572
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional ethics rounds concerning dialysis patients: staff’s ethical reflections before and after rounds

Abstract: The findings show the need for interprofessional reflective ethical practice but a balance between ethical reflection and problem solving is suggested if known patients are discussed. Further research is needed to explore the most effective leadership for reflective ethical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 29 publications
3
43
0
1
Order By: Relevance
“…Only three studies directly focused on support for ethical competence: ethics rounds from the viewpoint of ethical reflection (Svantesson et al . ,b) and a training programme including ethics round from the viewpoint of moral distress (Kälvemark Sporrong et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only three studies directly focused on support for ethical competence: ethics rounds from the viewpoint of ethical reflection (Svantesson et al . ,b) and a training programme including ethics round from the viewpoint of moral distress (Kälvemark Sporrong et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Staff meetings (Raines ), clinical ethics committees (Levine‐Ariff , Svantesson et al . ) and ethics rounds (Levine‐Ariff , Raines , Kälvemark Sporrong et al . , Svantesson et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One strategy that has proved efficient in this area is to develop so called 'ethics rounds', i.e., institutionalized, interprofessional ethics discussions on authentic patient cases in hospital settings [16]. Recent studies have reported that such rounds can be a working strategy to handle moral distress [22,40]. Interprofessional ethics rounds may be a suitable model also for research nurses and the staff they work with, but this has yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established that nurses can develop negative stress symptoms in situations where they assume they know the morally right thing to do, but organisational factors hinder them from following through upon the preferred action [23,36,45]. Studies have also indicated that moral distress can be reduced through competence strengthening, for example, in the form of interprofessional ethics rounds [22,40].…”
Section: Introductionmentioning
confidence: 99%